advertisement

For ease in using the definite integral, it is important to know its properties. Your book lists the following

1

(on the right, we give a name to the property):

(1)

(2)

(3)

(4)

(5)

Z a f ( x ) dx

Z b a f ( x ) dx a

Z

Z b f ( x ) dx a

Z b

Z a b

( f + g ) dx

C f ( x ) dx a b f ( x ) dx a

=

= 0

=

=

=

≤

−

Z a b f ( x ) dx integrating backwards

Z c

Z a b f ( x ) dx f ( x ) dx a

Z b

C

+

+ f ( x ) dx a

Z b g ( x ) dx if a

Z b

Z c b f ( x ) dx g ( x ) dx a f ( x ) ≤ g ( x interval addition linearity linearity

) on [ a, b ] estimation

Property (5) is useful in estimating definite integrals that cannot be calculated exactly.

Example 1.

Show that

Z

0

1 p

1 + x 3 dx < 1 .

3 .

Solution.

We estimate the integrand, and then use (6). We have x

3

Z

0

1 p

1 + x

3 dx

≤ x

≤ on [0 , 1];

Z

0

1 √

1 + x dx =

2

3

(1 + x )

3 / 2

1

0

=

2

3

(2

√

2 − 1) ≈ 1 .

22 < 1 .

3 .

(6)

We add two more properties to the above list.

Z b f ( x ) dx a

≤

Z b

| f ( x ) | dx .

a absolute value property

Property (6) is used to estimate the size of an integral whose integrand is both positive and negative (which often makes the direct use of (5) awkward). The idea behind (6) is that on the left side, the intervals on which f ( x ) is negative give a negative value to the integral, and these “negative” areas lower the overall value of the integral; on the right the integrand has been changed so that it is always positive, which makes the integral larger.

Example 2.

Estimate the size of

Z

0

100 e

− x sin x dx .

1 see Simmons pp. 214-215

1

2 PI. PROPERTIES OF INTEGRALS

Solution.

Z

A crude estimate would be

100

Z

100 e

− x sin x dx ≤ e

− x

| sin x | dx

0 0

≤

Z

0

100 e

− x dx, by (5), since | sin x | ≤ 1;

100

= − e

− x

= − e

−

100

+ 1 < 1 .

0

A final property tells one how to change the variable in a definite integral. The formula is the most important reason for including

Z b dx in the notation for the definite integral, that is,

Z b writing f ( x ) dx for the integral, rather than simply f ( x ), as some authors do.

a a

(7)

Z c d f ( u ) du =

Z a b f ( u ( x )) du dx dx,

u = c d

=

= u u (

( x a )

) u ( b ) .

,

, change of variables formula

In words, we can change the variable from u to x , provided we

(i) express du in terms of dx ; (ii) change the limits of integration.

2

There are various possible hypotheses on u ( x ); the simplest is that it should be differentiable, and either increasing or decreasing on the x -interval [ a, b ].

Example 3.

Evaluate

Z

0

1 du

(1 + u 2 ) 3

/

2 by substituting u = tan x .

Solution.

Proof of (7).

f ( u ): u = 0 , 1 corresponds to x = 0 , π/ 4; du = sec

2 x dx ; 1 + tan

2 x = sec

2 x ; thus

Z

0

1

(1 + du u 2 ) 3

/

2

=

Z

0

π/ 4 sec

2 x sec 3 x dx

=

Z

0

π/ 4 cos x dx = sin x

π/

4

=

√

2

2

.

We use the First Fundamental Theorem.

3

0

Let F ( u ) be an antiderivative of

Z

(8) F ( u ) = f ( u ) du ;

.

(9) d dx

F ( u ( x )) =

F ( u ( x )) = dF du

Z

· du dx f ( u ( x ))

= du dx f ( u ) dx .

du dx

, by the chain rule. So

Therefore

Z c d f ( u ) du = F ( d ) − F ( c ) , by the First Fundamental Theorem and (8);

= F ( u ( b )) − F ( u ( a )) =

Z a b f ( u ( x )) du dx dx, by the First Fundamental Theorem and (9).

Exercises: Section 3E

2 see Simmons p.339 for a discussion and an example

3 see Section FT